Double-stranded RNA induces disproportionate expression of thymic stromal lymphopoietin versus interferon- in bronchial epithelial cells from donors with asthma - Uller, L.; Leino, M.; Bedke, N.; Sammut, D.; Green, B.; Lau, L.; Howarth, P. H.; Holgate, S. T.; Davies, D. E. (Thorax, 2010)
Background Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine that strongly activates dendritic cells and can initiate allergic inflammation. Since exposure to rhinovirus or double-stranded (ds) RNA (a surrogate of viral infection) induces TSLP expression in bronchial epithelial cells (BECs), this cytokine may link innate antiviral responses and the type 2 adaptive immune response. Objective As BECs from donors with asthma have a deficient interferon (IFN) response to rhinovirus infection, a study was undertaken to test the hypothesis that their antiviral response shows a bias towards TSLP production. Methods Primary BECs were grown from subjects with asthma and healthy volunteers. After exposure to dsRNA, interleukin (IL)-8, IFNβ and TSLP mRNA and protein expression were measured by RT-qPCR and ELISA, respectively. Results dsRNA dose-dependently increased IL-8 expression in BECs with no significant difference between the groups. However, BECs from subjects with asthma expressed less IFNβ and more TSLP mRNA and protein in response to dsRNA than BECs from those without asthma (median (IQR) 57 (38-82) pg/ml vs 106 (57-214) pg/ml for IFNβ (p<0.05) and 114 (86-143) pg/ml vs 65 (32-119) pg/ml for TSLP (p<0.05) in response to 10 μg/ml dsRNA for 24 h). Induction of TSLP mRNA by dsRNA was blocked by Toll-like receptor 3 or protein kinase inhibitors or by preventing de novo protein synthesis, but not by neutralisation of type I IFN receptors. Conclusion BECs from subjects with asthma are biased towards higher TSLP and lower IFNβ production in response to dsRNA, suggesting that viral infection in asthma may lead to an altered mediator profile that biases towards a Th2 immune response.